Optimal social insurance with informal child care - HO, Christine (Institutional Knowledge at Singapore Management University, 2019)
The possibility of engaging in household child care may exacerbate the incentives of parents and grandparents to falsely claim disability benefits as households also get to save on formal child care costs. This paper considers a multi-generational family model with persistence in privately observed shocks and presents an efficient implementation case for subsidizing formal child care costs of the disabled. An implementation of the optimal scheme that consists of capped formal day care subsidies, non-linear income taxation and asset-testing is proposed. Simulations based on a parametrization that targets key features of the US labor and child care markets suggest that day care subsidies may lead to sizeable cost savings.